Effects of Senior Dance practice on the functional aspects of adults and the elderly - De Paula Venancio, Reisa Cristiane [UNESP]; do Carmo, Elisangela Gisele [UNESP]; De Paula, Luana Vanessa; Schwartz, Gisele Maria [UNESP]; Riani Costa, José Luiz [UNESP] (Editora Cubo, 2018)
This study aimed to identify and analyze the effects of Senior Dance practice on adults and elderly people. This is a descriptive, retrospective study that used the methodology of Systematic Review. Data collection occurred between August and October 2016, and studies were selected without restriction to time of publication. The search was conducted at the SciELO, Lilacs, Bireme, PubMed, and Scholar Google databases using the following descriptors: Dance, Dancing, Dance Therapy, and Therapy through Dance combined with the terms Senior Dance and Superior Dance. Twelve studies were selected. The investigations were related to the physical and functional aspects. There was prevalence of women (92%) and the age group from 60 to 69 years. Concerning the positive effects of the practice of Senior Dance, no significant changes were observed in only two of the studies. This review demonstrated that research involving Senior Dance reiterates its value associated with different variables. Although studies ratifying the positive impact of Senior Dance have been found, further studies focusing on the methodology for Senior Dance teaching and the investigation of subjective and affective-emotional aspects should be conducted in order to enable expansion of reflections on the health area and its applications to different contexts and populations.
Efeitos da prática de Dança Sênior nos aspectos funcionais de adultos e idosos
Keywords: Aged; Dance Therapy; Dancing; Motor Activity; Physical Fitness